Digital Service Trade and the Wage Income Gap Between Urban and Rural Residents: Empirical Evidence from China - Weixiao Lu; Wenhua Yuan (SAGE Open)
While promoting the high-quality development of foreign trade, digital service trade has also had a complex and far-reaching effect on the wage income gap between urban and rural residents. On the basis of Chinese provincial data from 2009 to 2019, this study uses the fixed effect model and the Difference-in-Differences(DID) model for empirical analysis. The development of digital service trade significantly reduces the wage income gap between urban and rural residents. The development of digital service trade can effectively improve resource allocation efficiency, promote industrial structure optimization and upgrading, and enhance agricultural total factor productivity. In areas with high levels of digital inclusive finance, education resources and marketization, the effect of digital service trade development on narrowing the wage income gap between urban and rural residents is more prominent. The innovative development pilot policy of service trade carried out by the Chinese government in 2016 promoted the development of digital service trade and narrowed the wage income gap between urban and rural residents in the pilot provinces. The conclusions of this study provide a reference for the government to leverage the development of digital service trade to narrow the income gap between urban and rural residents in the future.